Comparative Synthesis and Characterization of Nanostructured SAPO-34 Using TEA and Morpholine: Effect of Mono vs. Dual Template on Catalytic Properties and Performance toward Methanol to Light Olefins - Aghamohammadi, Sogand; Haghighi, Mohammad; Sadeghpour, Parisa; Souri, Tayebeh (Combinatorial Chemistry & High Throughput Screening, 2021)
Aim and Objective: Production of light olefins from methanol was studied over SAPO-34 molecular sieves exploring the effect of mono and dual templates. Herein, the single templates of TEA, morpholine, and mixed templates of TEA/morpholine (equal molar ratio of TEA and morpholine) were used to synthesize SAPO-34 catalysts. Materials and Methods: The prepared samples were prepared via hydrothermal synthesis method and characterized with XRD, FESEM, PSD, EDX, BET, and FTIR techniques. Results: It was found that the crystallinity decreased upon applying TEA as a template and it can also be noted that the intensity of the SAPO-34 phase peaks increased by increasing the morpholine in template mixture. Production of much smoother particles for the catalyst synthesized with a binary template mixture of TEA/morpholine can be dependent on the crystallinity increase. Si incorporation value was decreased for the catalyst with a major phase of SAPO-5 (topological structure of AFI). It is indicative that the TEA application would facilitate the formation of AFI structure, which is incapable of incorporating higher amounts of Si into the crystalline framework. Conclusion: The nature of the template determines the morphology of the final product due to the different rates of crystal growth obtained in accordance with XRD and FESEM results. Therefore, the catalyst synthesized with the TEA/morpholine mixture shows the best performance among synthesized samples in terms of lifetime in the MTO process, sustaining light olefins selectivity at higher values (about 90% after 630 min TOS).
Keywords: ethylene